Learning curve and complications of unilateral biportal endoscopy–unilateral laminectomy bilateral decompression for lumbar spinal stenosis - Jiashen Shao; Zihan Fan; Hai Meng; Qi Fei (Videosurgery and Other Miniinvasive Techniques)
Introduction: The unilateral biportal endoscopic (UBE) technique has been widely adopted for treatment of lumbar disc herniation and lumbar spinal stenosis. Understanding its learning curve, as well as the factors that influence perioperative complications, is crucial for mastering and effectively learning this technique.